THE ROLE OF LEADERSHIP AND SOFT-SKILLS COMPETENCIES OF THE PERFORMANCE AT THE FACILITY AND CONSTRUCTION UNIT INDONESIAN ARMED FORCES - Anggraini, Widya Arti; Sukamdani, Nugroho B; Sukwika, Tatan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
One of the work units under the Indonesian Armed Forces Headquarters Detachment (Detasemen Markas Besar Tentara Nasional Indonesia or Denma Mabes TNI) organization is the Facility and Construction Unit of Indonesian Armed Forces known as the Facility and Construction of Indonesian Armed Forces. The Facility and Construction of the Indonesian Armed Force shipment of construction materials have been delayed as a result of the COVID-19 outbreak. Furthermore, the working-from-home (WFH) implementation affects the restrictions on collaboration and communication between leaders and participants. The existence of a leadership role supported by good soft-skills competencies, and career development, is expected to improve the performance of Indonesian Armed Force members. This study aims to determine the actual impact of leadership, soft-skills competencies, and career development on the performance of TNI members at the Facility and Construction of the Indonesian Armed Force. The study's findings revealed that soft-skills competencies and leadership characteristics directly impacted member performance. Additionally, a strong direct impact on professional development and soft-skills competencies on career development was discovered. It is well-organized that the leadership variable's influence on performance during career growth is insignificant in the indirect effect. On the other hand, the soft-skills competencies variable has a major impact on performance across career growth. This study concludes that organizational members' career growth and performance can be influenced by leadership and soft-skills competencies in the facility Construction of the Indonesian Armed Forces while leadership characteristics have no substantial impact on performance, career development as an intervening variable has a considerable impact on soft-skills competencies. Organizational performance improvement policies can be achieved through the career development of Indonesian Armed Forces (TNI) members. Capacity-building efforts can focus on leadership and soft-skills competencies.Â 